1993
DOI: 10.22358/jafs/69860/1993
|View full text |Cite
|
Sign up to set email alerts
|

Somatic cell count in quarter foremilk of cows from small herds with a high level of subclinical mastitis

Abstract: Aseptic foremilk samples of 213 cows from 77 small farms were collected. Of 852 samples, 65.5% were infected. The most frequently isolated pathogens were Streptococcus agalactiae (22.7%), Staphylococcus aureus (18.8%) and Staphylococcus epidermidis (18.3%). Somatic cell count (SCC, in thousand/ml) in foremilk samples, determined by Fossomatic, ranged significantly (P<0.01) between bacteria from 313' (non-infected) to 2128' cells/ml (infected by Streptococcus species). A high percentage of infected samples with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Based on experimental data where milk somatic cell numbers of individual udder quarters were identified simulataneously by quantitative and semi-quantitative tests and data were compared consecutively, the CMT showed high sensitivity and specificity and the results gave high correlation values (r = 0.6 to 0.8) with those gained by quantitative tests (GALTON et al, 1979;OKELLO-UMA and GIBSON, 1979;BATRA and MCALLISTER, 1984;PEDNEKAR et al, 1992;FANDREJEWSKA, 1993;BRITO et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Based on experimental data where milk somatic cell numbers of individual udder quarters were identified simulataneously by quantitative and semi-quantitative tests and data were compared consecutively, the CMT showed high sensitivity and specificity and the results gave high correlation values (r = 0.6 to 0.8) with those gained by quantitative tests (GALTON et al, 1979;OKELLO-UMA and GIBSON, 1979;BATRA and MCALLISTER, 1984;PEDNEKAR et al, 1992;FANDREJEWSKA, 1993;BRITO et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations were made by Bolgov et al (2002), who stated that besides factors such as age, production level and season of lactation, the occurrence of mastitis also depends on the udder characteristics. That mastitis is a great enemy of the dairy industry was shown by a research performed in Poland (Fandrejewska, 1993) during which it was shown that over 65.5% of milk samples collected at 77 dairy farms were infected with pathogenic microorganisms.…”
Section: Discussionmentioning
confidence: 99%